Factors associated with diabetic retinopathy among patients with diabetes in rural Guangxi, China: a multicenter cross-sectional study - Xian, Xiaomin; Chen, Jingfeng; Li, Ziqiang; Zheng, Qiuping; Lei, Xiaoxue; Bai, Chaoqun; Zhang, Yanping; Fu, Guifen (Frontiers in Endocrinology, 2026)
ObjectiveThe primary objective of this study was to estimate the prevalence of diabetic retinopathy (DR) among adult patients with diabetes in rural Guangxi. The secondary objective was to identify demographic, clinical, and psychosocial factors associated with DR. These findings could offer practical evidence for improving diabetes management in remote areas.MethodsFrom January to July 2022, this population-based multicenter cross-sectional study employed a multi-stage stratified sampling method. Initially, five cities were randomly selected within the region. Next, three counties were randomly chosen from each city, totaling 15 counties. Data on sociodemographic characteristics, diabetes-related factors, and laboratory indicators were collected using questionnaires and clinical examinations. DR was assessed through dilated fundus examination or fundus photography. Multivariable logistic regression was performed to estimate adjusted odds ratios (ORs) and identify factors associated with DR.ResultsA total of 2,178 patients with diabetes were included, comprising 1,204 males (55.28%) and 974 females (44.72%), with a mean age of 63.25 ± 12.71 years. The prevalence of DR among people living with diabetes in rural Guangxi was 22.36% (95% CI: 20.62%–24.10%). Multivariate logistic regression analysis revealed that advanced age (OR = 1.015, 95%CI: 1.001–1.029, P = 0.042), increased HbA1c levels (OR = 4.004, 95% CI: 3.435–4.666, P < 0.001), and elevated triglyceride levels (OR = 1.493, 95% CI: 1.267–1.758, P < 0.001) were significantly associated with the development of DR in patients with diabetes.ConclusionThe prevalence of DR among people living with diabetes in rural Guangxi was 22.36%. This finding underscores the importance of healthcare providers closely monitoring older adults and patients with elevated HbA1c and triglyceride levels.